PERBANDINGAN KINERJA PEMASARAN KUBIS DI KECAMATAN MERDEKA DENGAN KECAMATAN TIGAPANAH KABUPATEN KARO PROVINSI SUMATERA UTARA - Indrawaty Sitepu; Nurmely Violita Sitorus (Majalah Ilmiah METHODA, 2019)
This study aims to determine the differences in the performance of cabbage marketing in the Subdistrict of Merdeka with the Subdistrict of Tigapanah, Karo District, North Sumatra Province. Determination of the study area was done purposively (intentionally), where the two regions were centers of cabbage production in Karo District, North Sumatra Province. The method for determining producer samples is quota sampling and traders are accidental sampling. Data analysis methods are tabulated according to the type, namely descriptive, marketing margins, farmer's share. The research was conducted in February-March 2018. The results showed: The cabbage marketing channels in Merdeka Subdistrict consisted of two channels while the Tigapanah Subdistrict consisted of three channels; cabbage marketing margins in Tigapanah Subdistrict are more efficient than Merdeka Subdistrict; the portion obtained by cabbage farmers (farmer’s share) in the Tigapanah Subdistrict is higher than Merdeka Subdistrict even though both are inefficient.